Onomastic culture-specific term of the Arab world in rhyming slang - Yuri V. Gorshunov; Elizaveta Y. Gorshunova (Этническая культура)
The article is devoted to the national and ethnic component of rhyming slang. The work focuses on the culture-specific terms of rhyming slang, reflecting the specific terms of Arab culture. The purpose of the study is to consider rhymes in linguistic and socio-cultural aspects, the names of which are associated with the countries and specific terms of the Arab world. The main research method is descriptive, implemented in the techniques of systematization, generalization and interpretation of linguistic material. Linguistic methods include contextual, definitional analysis and the method of semantic interpretation. The authors focused on a special layer of stylistic vocabulary, reflecting cultural, socio-cultural and cultural-historical specific terms in the context of cultural literacy and possessing linguacultural value. The research field included both obsolete rhymes that arose in the mid-19th century and established rhymes dating back to the 20th century, as well as relatively new rhymes dating back to the beginning of the new millennium. According to the research, onomastic rhymes based on precedent names dominate in speech with rhymed slang. The results of the research may be useful and interesting for specialists developing the topics of intercultural communication, linguacultural studies, linguastylistics, contrastive linguistics of English and Russian, and lexicology.